Polymerised superparamagnetic antigen presenting cell lymphocyte capture for enriching tumour reactive T-cells and neoantigen identification - Chung-Yao Hsu; Po-Cheng Tsai; Jung-Chen Lin; Chen-Hsueh Pai; Yun-Jui Teng; Bing-Yu Yao; Cheng-Yin Fei; Gwo Harn Max Shiau; Leon CW Lin; Sean Lo; Hung-Chih Yang; Che-Ming Jack Hu (Nature Communications)
Abstract Ultrasensitive antigen recognition between T lymphocytes and cognate targets via immunological synapse (IS) formation enables live cell-based antigen-specific T cell detection. However, unpredictable antigen processing and major histocompatibility complex (MHC) turnover limit specificity. Here, intracellularly polymerized antigen-presenting cells (pAPCs) are developed for modular, persistent antigen display via kinetically driven loading. Although inanimate, pAPCs mimic cellular interactions, inducing IS hallmarks such as supramolecular activation cluster formation, cytoskeletal contraction, and trogocytosis. Incorporation of superparamagnetic nanoparticles allows label-free magnetic isolation of antigen-specific T cells, surpassing MHC-conjugated beads in sensitivity and specificity. In tumor-bearing hosts, pAPCs enrich tumor-reactive lymphocytes, enhancing adoptive T cell therapy and neoantigen-specific T cell identification. Additionally, pAPCs from engineered cells expressing monovalent human MHC enrich virus- and tumor-specific CD8 T cells from human peripheral blood mononuclear cells and human leukocyte antigen-transgenic mice, demonstrating the potential of this cell–gel hybrid platform for precise antigen-specific T cell capture.